2017
DOI: 10.1007/s12603-016-0831-x
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in hospitalised older adults: A multicentre observational study of prevalence, associations and outcomes

Abstract: These findings support the prioritisation of nutritional screening in clinical practice and public health policy, for all patients ≥70 on admission to hospital, and in particular for people with dementia, increased functional dependency and/or multi-morbidity, and those who are frail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 40 publications
5
69
0
3
Order By: Relevance
“…Malnutrition can be caused by starvation, chronic disease-related inflammation and acute disease-related inflammation (2) . The prevalence of malnutrition varies widely among hospitalised adults, with estimates ranging from 4% to 45% (3)(4)(5)(6)(7)(8) . Multiple studies report adverse effects of malnutrition, which include a prolonged length of stay (5)(6)(7) , increased overall and in-hospital mortality (5)(6)(7) , increased risk of readmission (6,7,9,10) and higher hospitalisation costs (6,10) .…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition can be caused by starvation, chronic disease-related inflammation and acute disease-related inflammation (2) . The prevalence of malnutrition varies widely among hospitalised adults, with estimates ranging from 4% to 45% (3)(4)(5)(6)(7)(8) . Multiple studies report adverse effects of malnutrition, which include a prolonged length of stay (5)(6)(7) , increased overall and in-hospital mortality (5)(6)(7) , increased risk of readmission (6,7,9,10) and higher hospitalisation costs (6,10) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, slightly lower results compared to the present study were obtained in a Singaporean study by Pin Ng et al . , where, among 1550 patients (62% of females and 38% of males) older than 55 years, malnutrition was reported in approximately 35% of patients diagnosed on the basis of serum Alb concentration and in 5% on the basis of TLC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that malnutrition is associated with rapid cognitive decline, disease progression and the degree of impairment in daily functioning in patients with dementia [8][9][10]. While studies have shown that patients with dementia or AD were more likely to suffer from a poor nutritional status [11,12]. Weight loss and malnutrition were prominent symptoms of dementia and could be detected at the early stages of AD [13,14].…”
Section: Introductionmentioning
confidence: 99%